Helicobacter pylori infection and inflammatory bowel disease: is there a link? - Nejabat, Maryam; Zadeh Fard, Saeid Amiri; Safarpour, Alireza; Ahmadpour Jirandeh, Somayeh (Revista Publicando, 2018)
Inflammatory bowel disease (IBD) that include Crohn ´s Disease (CD) and Ulcerative colitis (UC) are types of digestive system disease that steel have not been properly identified as their original causes. Our goal was to evaluation of lower infection with H.pylori in patients suffer from IBD in compete with the normal population. Method: IN this case-control study 146 patients with IBD (32 with CD and 114 with UC) and 146 volunteers donated blood as control group were tested for IgG and IgA antibody against H.pylori since Dec 2017 from May 2018 in Shiraz that were randomly selected   from IBD registry software in motahari clinic. Result: The presence of H.pyloriIgG   was confirmed in 10 (31.2%) of CD, 37 (32.4%) of patients with ulcerative colitis and 105 (71.9%) of the control group that it was significant (P< 0.001).The presence of H.pylori IgA   was confirmed in 25%of CD, 31.6% of patients with UC and 40.4% of the control group that it was not significant. In order to relation between IBD treatment regimens and presence of H.pylori IgG, there was significant differences between patients who received immune-modulator and immune-suppressive drugs and whom were not used these drugs.(p< 0.001). Conclusion: Our results show that the prevalence of serum IgG antibody against H pylori was significantly lower in patients with IBD than in controls. The use of immune-modulator and immune-suppressive drugs may reduce the involvement of IBD patients with Helicobacter pylori infection.